EXPLORING THE IMPACT OF ARTIFICIAL INTELLIGENCE IN THE VISUAL ARTS: A COMPREHENSIVE STUDY - Ezhilmurugan., P.; E, Yashavini (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Human thinking first appeared through visual art. From the early cave man paintings to this modern-day AI-generated image and deep learning algorithms, the world has developed. Artificial intelligence (AI) has impacted the visual arts in various ways, and it has influenced more and more as a transformative force in many fields. Through this study, the complex link between artificial intelligence and the visual arts is explained by analyzing the effects, the outcomes, and the future paths. The study explores how artificial intelligence has transformed the production, interpretation, and consumption of art. It also shows how AI algorithms are employed by artists to generate imagery. This study, along with the analysis of surveys, experimental initiatives, and different artworks, explains the impact of artificial intelligence in the world of visual arts. It also tells how artificial intelligence has swayed historical mythology and its sociocultural ramifications. With an interdisciplinary approach, this study integrates the understanding of computer science, art history, and cultural studies and offers a subtle analysis of the profound impact of AI on the visual arts. Finally, this comprehensive study provides an insight on how artificial intelligence has influenced and impacted the visual arts and about the evolutionary technological potential of it in the future by providing a deeper and better understanding of the growing complex link between creativity and technology in modern art practices.